Search for anomalous heavy-flavor quark production in association with W bosons - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Agelou, M.; Agram, J. L.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; et al. (American Physical Soc, 2005)
We search for anomalous production of heavy-flavor quark jets in association with W bosons at the Fermilab Tevatron p(p) over bar Collider in final states in which the heavy-flavor quark content is enhanced by requiring at least one tagged jet in an event. Jets are tagged using one algorithm based on semileptonic decays of b/c hadrons, and another on their lifetimes. We compare e+jets (164 pb(-1)) and mu+jets (145 pb(-1)) channels collected with the D0 detector at root s = 1.96 TeV to expectations from the standard model and set upper limits on anomalous production of such events.